PROPOLIS SEBAGAI SUPLEMEN BAGI PENDERITA TUBERKULOSIS DEWASA - Pranandaru, Herlambang; Sembodo, Adi; Choirina, Julia; Wijaya, Fahrizal Kusuma; Sewaka, Septian Wisnu (Program Kreativitas Mahasiswa - Penelitian, 2013)
One of current world health problems is tuberculosis. Propolis can inhibit M. tuberculosis growth and increase the mediator of macrophage activator. The aim to proof that propolis as a supplement to heal in tuberculosis.Â  Research design is control experimental group, using 15 samples patient of positive BTA, divided into 2 groups, control (standard anti-tuberculosis) and experiment (combination of standard anti-tuberculosis+propolis). All patients randomly, take the propolis or placebo with 4 drops dosage every day during 2 month and BTA will be checked. The examination result shows that experiment group has better recovery than control group (p=0,020). It concluded that propolis can be a good choice as a supplement of treating infections caused by M.tuberculosis.Keywords: Propolis, Supplement, Recovery, Adult patient of tuberculosis.